The Influence of Principal Leadership on Teachers’ Performance in SMA Negeri at Kayuagung District - Susanti, Eva (Journal of Social Work and Science Education, 2023)
This study aimed to determine the influence of the principal's leadership on teachers’ performance in SMA Negeri at Kayuagung District. This research was conducted for five months, from May 2022 to September 2022. The research method used in this research is a quantitative descriptive method. The number of samples in this study was 120, which were taken through the probability sampling technique. Data collection techniques in this study used questionnaires, documentation, and interviews. Data analysis was performed using regression analysis with the help of SPSS 22.00 for Windows. Based on the regression test results, the t-count value is 8,469 > the t-table price of 1,657, where the t-count price is greater than the t-table, so Ho1 is rejected. Thus, it can be concluded that the principal's leadership significantly influences teacher performance in SMA Negeri at Kayuagung District. This also shows that the principal's leadership has a major role in teacher performance and managing learning in schools. Based on the findings in this study, it is suggested that school principals strive to improve their competence so that the principal's leadership function can be carried out optimally and that it can encourage increased teacher performance in schools.